Mega Events and Mobility: the impacts on the quality of the urban environment - Galderisi, Adriana (TeMA - Journal of Land Use, Mobility and Environment, 2008)
According both to the relevant transformations and to the potential impacts on the natural resources induced by the Olympic Games in the hosting cities, in the last fifteen years many efforts have been undertaken by the International Olympic Committee to promote sustainable principles within Olympic Games and to guarantee a positive and durable legacy to the hosting cities, contributing also to the improvement of the quality of urban environment. Nevertheless, the increasing diffusion of terms such as Green Olympics o Sustainable Olympics risk to become just a new “brand” for promoting the hosting cities in the global competition arena instead of being translated in effective tools for driving choices and interventions. Hence, based on the comparison among some past and future Olympic cities, the relevance and the main outcomes of the policies aimed at promoting sustainability have been examined, mainly focusing on that ones able to encourage a sustainable urban mobility. The latter in fact, still dominated by the private cars, is at present largely recognized as one of the main causes of the decreasing quality of the urban environment and, in the meanwhile, the increase of the demand for mobility, highly concentrated in time and space, is one of the most relevant issue in the Olympic Games’ organization. Finally, grounding on current tendencies, some guidelines for re-addressing urban mobility policies towards sustainability in case of Mega-Events have been outlined.